Ulinastatin protects against myocardial ischemia/reperfusion injury in rats via Rho/ROCK signaling pathway: Ulinastatin protects against myocardial IRI - Liu, Ling; Liu, Jun; Wang, Junshuai; Chen, Yu; Liu, Gang (Cellular and Molecular Biology, 2023)
We aimed to study the influences of ulinastatin on diseased myocardial tissues, cardiomyocyte apoptosis and inflammatory reaction in rats with myocardial ischemia/reperfusion injury (IRI) via the Ras homolog (Rho)/Rho-associated kinase (ROCK) signaling pathway and its mechanism. The rats were randomly divided into three groups: control group (C group), IR model group (IR group) and IR model + ulinastatin treatment group (UR group). The pathological changes in myocardial tissues were detected via HE staining, the markers of myocardial injury were examined using kits, and apoptosis was determined through TUNEL assay. Moreover, ELISA was applied to measure the expressions of TNF-α, interleukin-6 (IL-6) and IL-8 in cardiac tissues, and Western blotting was performed to detect the protein expression levels of RhoA, ROCK2 and MLCP. The myocardial infarction area in the IR group was markedly larger than that in the C group (P<0.01) but was significantly reduced after ulinastatin treatment (P<0.05), and the IR group had higher levels of AST, cTnI, CK-MB and LDH than C group, but the levels of those indexes were significantly reduced after ulinastatin treatment.The cardiomyocyte apoptosis was increased in the IR group compared with that in the C group, while it was decreased in the UR group in comparison with that in the IR group. Besides, the UR group exhibited lowered expression levels of the Rho/ROCK signaling pathway-related proteins compared with the IR group. Ulinastatin may ameliorate the prognosis of rats with myocardial IRI via the Rho/ROCK signaling pathway.